Chaplin, the collection - Chaplin, Charles (Madacy Music Group [distribución])
Este volumen incluye tres cortometrajes dirigidos por Chaplin: Charlie on the ocean (Essanay, 1915), Getting acquainted (Keystone, 1914), Mabel's married life (Keystone, 1914); George Nicholls dirigió uno: The landlady's pet 1914).